Assessment of a newly designed double-barreled bullet-shooting stunner for adequate stunning of water buffaloes. (November 2022) - Gascho, Dominic; Stephan, Roger; Bauer, Clemens; Oesch, Michelle Aimée; Richter, Henning
Abstract: To ensure animal welfare at slaughter, rapid stunning is required to render the animal deeply unconscious. In cattle, captive-bolt stunners are typically used for this purpose. However, with regard to their impact force and maximum length of approximately 120 mm, such captive-bolt stunners are not suitable for stunning water buffaloes due to anatomical characteristics of the skull. In water buffaloes the bone layer is thicker and the distance from the point of attachment of the captive-bolt stunner to the relevant brain region is longer. For this reason, a special bullet-shooting stunner was developed, which is similar in size and handling to a standard captive-bolt stunner, but instead of a bolt, it fires a bullet. Actually, even two bullets can be loaded so that a follow-up shot can be fired immediately if necessary. In this study, the bullet-shooting stunner was tested using two different types of hunting ammunition for stunning water buffaloes during regular slaughter. Graphical abstract: Unlabelled Image